What Is the Evidence Base Linking Gender with Access to Forests and Use of Forest Resources for Food Security in Low- and Middle-Income Countries? A Systematic Evidence Map - Kimanzu, N.; Schulte-Herbrüggen, B.; Clendenning, J.; Chiwona-Karltun, L.; Krogseng, K.; Petrokofsky, G. (MDPI, 2021)
In nearly all parts of the world, an important part of people’s livelihood is derived from natural resources. Gender is considered one of the most important determinants of access and control over forests. It is thought that women and men within households and communities have different opportunities and different roles and responsibilities in relation to forest use. It is probable that when women have equal access to forests, better food security outcomes can be achieved for individuals and households that are dependent on forests for their livelihoods. A systematic evidence map of the evidence base linking gender with access to forests and use of forest resources for food security was undertaken. Ten bibliographic databases and 22 websites of international development and conservation organisations were searched using keywords suggested by stakeholders. Other articles were found by emailing authors and organisations to send potentially relevant publications. 19,500 articles were retrieved from bibliographic databases and 1281 from other sources. After iterative screening, 77 studies were included: 41 focussed on Africa, 22 on Asia, 12 on Latin America, 2 were global. Most indicators of food security measure access to food, measured by total consumption, expenditure, or income. Studies showed strong gender specialisation: commercial access and utilisation of forests and forest products dominated by men, whereas access for subsistence and household consumption is almost exclusively the task of women. Despite the large number of studies reviewed, limitations of the evidence base, including methodological heterogeneity, a dominance of case studies as the study design, and unequal geographical representation in study locations, make it difficult to generalise about the overall importance of gender and its effect on access to and use of forests for food security in developing countries. The critical gaps in the evidence base include geographical representation in primary research and a greater breadth of study designs to assess gender implications of access to forest resources globally.